Profiling the concept of TRAUMA in English-language educational discourse - Molhamova, Liliia; Tatsenko, Nataliia; Karpov, Oleksandr (Cognition, Communication, Discourse, 2026)
The article presents a linguo-cognitive analysis of the profiling of the concept of TRAUMA in English-language educational discourse. The relevance of the study is determined by the increasing role of traumatic experience in contemporary society and the integration of the trauma-informed approach into educational practices. The aim of the study is to identify the specific features of the actualization of the core and peripheral attributes of the concept TRAUMA within the institutional educational environment and to determine the cognitive mechanisms underlying its profiling. The theoretical and methodological framework is grounded in cognitive semantics, conceptual metaphor theory, discourse analysis, and linguoconceptology. The research material includes dictionary definitions, online courses, academic textbooks, and scholarly articles on trauma-informed education. The study reconstructs a multi-level frame model of the concept TRAUMA, encompassing the following profiles: prototypical (injury), clinical (diagnosis and symptomatology), neurobiological (embodied memory), therapeutic (recovery), pedagogical (educational environment), and socio-relational (disrupted connections). It is established that dictionary discourse fixes the medical-physical core of the concept, whereas educational discourse performs its functional re-profiling, from a category of pathology to a category of pedagogical responsibility, safety, and support. Within the trauma-informed approach, trauma is interpreted as a contextual factor that shapes communicative strategies, ethical standards, and institutional practices. The study demonstrates that the profiling of the concept TRAUMA is selective in nature: features such as regulation, resilience, empathy, and inclusivity are foregrounded, while purely clinical aspects shift to the periphery. Metaphorical models TRAUMA AS WOUND, BURDEN, JOURNEY perform both cognitive and pragmatic functions, enabling an empathetic reinterpretation of learners’ behavioral manifestations. The findings indicate a transformation of the semantic core of the concept TRAUMA in English-language educational discourse and its integration into the system of pedagogical ethics.